Fiber composite diaphragm as well as preparation method and application thereof

Through the design of fiber composite separators, combined with polymer and inorganic nanoparticle composite polymer materials, the problems of insufficient safety and electrochemical performance of existing lithium-ion battery separators under high temperature and abnormal conditions are solved, and excellent thermal safety is achieved and electrochemical properties.

CN119231102APending Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310799575.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators cannot effectively prevent explosion and combustion under high temperature and abnormal conditions, and the electrochemical performance is insufficient, which cannot meet the demand of the power battery market.

Method used

A fiber composite separator is adopted, including a porous membrane layer of polymer A, a core-shell structure fiber membrane layer and a bonding layer. Polymer A is selected from trans-1,4-polyisoprene, inorganic nanoparticle composite polymer C and D, and polymer B bonding layers, were prepared by vulcanization treatment and coaxial electrospinning technology.

Benefits of technology

It achieves excellent electrochemical performance and thermal safety performance. The diaphragm automatically closes the hole to protect the battery when the temperature rises, and restores the channel after cooling to ensure the normal operation of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004319315600000161
    Figure BDA0004319315600000161
  • Figure BDA0004319315600000162
    Figure BDA0004319315600000162
  • Figure BDA0004319315600000171
    Figure BDA0004319315600000171
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, and discloses a fiber composite diaphragm and a preparation method and application thereof, the diaphragm comprises a polymer A porous membrane layer, a fiber membrane layer and a bonding layer located between the polymer A porous membrane layer and the fiber membrane layer; the polymer A is selected from at least one of trans-1, 4-polyisoprene, butadiene rubber, natural rubber, butadiene styrene rubber, polyurethane, high-density polyethylene and a styrene-butadiene-styrene block copolymer; the fiber membrane layer is formed by core-shell structure fibers, the bonding layer is made of a polymer B, and the polymer B is selected from at least one of polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate. The diaphragm provided by the invention has excellent electrochemical performance such as cycle performance and rate performance and thermal safety performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a fiber composite diaphragm and a preparation method and application thereof. Background Art

[0002] In lithium batteries, the diaphragm refers to the isolating material between the positive and negative electrodes of the battery. Its main function is to isolate the positive and negative electrodes of the battery so that the electrons in the battery cannot pass freely, but allows the ions in the electrolyte to pass freely between the positive and negative electrodes. It is a key component of the battery. As one of the most critical core materials of lithium batteries, it has an important impact on the electrochemical performance of the battery. At the same time, because power batteries have higher operating temperatures and more complex driving environments, they may explode and burn in unconventional states, that is, abnormal charging and discharging states, abnormal heat and abuse of mechanical conditions. Therefore, the thermal safety performance of power lithium-ion batteries is particularly important. However, the lithium-ion battery diaphragms currently used commercially are polypropylene (PP) and polyethylene (PE) diaphragms, which can no longer fully meet the requirements of the growing power battery market.

[0003] Therefore, the need for diaphragm materials with both excellent electrochemical properties and thermal safety performance has become one of the technical problems that urgently need to be solved in this field. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and to provide a fiber composite diaphragm material having both excellent thermal safety performance and electrochemical performance.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a fiber composite diaphragm, which comprises a polymer A porous membrane layer, a fiber membrane layer and a bonding layer located between the polymer A porous membrane layer and the fiber membrane layer;

[0006] Wherein, the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene, and styrene-butadiene-styrene block copolymer;

[0007] The fiber membrane layer is formed by core-shell structure fibers, the material of the core layer fibers of the core-shell structure fibers is a polymer C-inorganic nanoparticle composite formed by a composite of inorganic nanoparticles and a polymer C, the material of the shell layer fibers of the core-shell structure fibers is a polymer D, and the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate;

[0008] The material of the bonding layer is polymer B, and the polymer B is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate.

[0009] A second aspect of the present invention provides a method for preparing a fiber composite diaphragm, the method comprising:

[0010] (1) subjecting component G containing polymer A to a vulcanization treatment to obtain a polymer A porous membrane, wherein the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene, and styrene-butadiene-styrene block copolymer;

[0011] (2) coating a dispersion I containing polymer B on one side of the polymer A porous membrane to form a bonding layer on one side of the polymer A porous membrane to obtain a precursor I;

[0012] (3) introducing a dispersion II containing a polymer C and inorganic nanoparticles and a dispersion III containing a polymer D into a storage device provided with an inner needle and a storage device provided with an outer needle of a coaxial electrospinning device, respectively, and performing coaxial electrospinning with the precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, wherein the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate;

[0013] (4) Drying the precursor II to obtain a fiber composite diaphragm.

[0014] The third aspect of the present invention provides a fiber composite diaphragm prepared by the aforementioned method.

[0015] A fourth aspect of the present invention provides use of the aforementioned fiber composite separator in a lithium ion battery.

[0016] The fiber composite diaphragm material provided by the present invention not only has excellent electrochemical properties such as cycle performance and rate performance, but also has excellent thermal safety performance. In particular, it can be seen from the air permeability test that the diaphragm material provided by the present invention can automatically close the pores when the temperature rises, for example, 110°C, thereby blocking the electrolyte to protect the battery, and when the temperature drops again, the diaphragm can open the channel again, allowing the battery to resume normal operation. Therefore, it has both excellent electrochemical performance and thermal safety performance.

[0017] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] As mentioned above, the first aspect of the present invention provides a fiber composite diaphragm, which comprises a polymer A porous membrane layer, a fiber membrane layer, and a bonding layer located between the polymer A porous membrane layer and the fiber membrane layer;

[0020] Wherein, the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene, and styrene-butadiene-styrene block copolymer;

[0021] The fiber membrane layer is formed by core-shell structure fibers, the material of the core layer fibers of the core-shell structure fibers is a polymer C-inorganic nanoparticle composite formed by a composite of inorganic nanoparticles and a polymer C, the material of the shell layer fibers of the core-shell structure fibers is a polymer D, and the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate;

[0022] The material of the bonding layer is polymer B, and the polymer B is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate.

[0023] According to the method described in the second aspect of the present invention, preferably, the polymer A is selected from at least one of trans-1,4-polyisoprene, high-density polyethylene, and styrene-butadiene-styrene block copolymer. According to a more preferred embodiment of the present invention, the polymer A is a composition of trans-1,4-polyisoprene and high-density polyethylene. The inventors of the present invention have found that when a combination of trans-1,4-polyisoprene and high-density polyethylene is specifically selected as polymer A, the diaphragm material obtained by combining the polymer A porous membrane layer with the fiber membrane layer and the bonding layer has better thermal safety performance.

[0024] Preferably, when polymer A is a composition of trans-1,4-polyisoprene and high-density polyethylene, based on the total weight of the composition as 100 parts by weight, in the composition, the weight ratio of the high-density polyethylene to the trans-1,4-polyisoprene is 50-90:10-50, more preferably 60-90:10-40, for example, 60:40, 70:30, 80:20, 90:10.

[0025] Preferably, the density of the high-density polyethylene is 0.94-0.96 g / cm 3 .

[0026] Preferably, in the trans-1,4-polyisoprene, the content of the trans-1,4-structural unit is 90-99 wt %.

[0027] According to a preferred embodiment of the present invention, the polymer A porous membrane is obtained by subjecting component G containing polymer A to a vulcanization treatment.

[0028] Preferably, the component G further contains water-soluble salt, sulfur and stearic acid. Relative to 100 parts by weight of the polymer A, the amount of sulfur is 0.5-2 parts by weight, the amount of stearic acid is 0.5-2 parts by weight, and the amount of the water-soluble salt is 1-6 parts by weight.

[0029] Preferably, the water-soluble salt is sodium chloride or potassium chloride; according to the present invention, preferably, in the component G, based on 100 parts by weight of the component G, the weight ratio of the polymer A to the water-soluble salt is (94-99): (1-6).

[0030] Preferably, the vulcanization treatment operation includes vulcanizing and drying the component G in sequence.

[0031] Preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, wherein the conditions of the first vulcanization include: temperature 150-200°C, pressure 5-20MPa, time 5-50 minutes; the conditions of the second vulcanization include: temperature 10-50°C, pressure 5-20MPa, time 5-50 minutes.

[0032] Preferably, the drying conditions include: a temperature of 60-100° C. According to the present invention, the drying is preferably performed under vacuum conditions.

[0033] According to the present invention, preferably, before the drying, the sample obtained by sulfidation is first ultrasonically cleaned until the residual water-soluble salts in the sample are dissolved, and then the drying treatment is performed. The present invention has no special restrictions on the specific operation of the ultrasonic cleaning, as long as the residual water-soluble salts in the sample obtained by the sulfidation treatment can be dissolved.

[0034] Preferably, the polymer B is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate. More preferably, the polymer B is selected from at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex and carboxymethyl cellulose.

[0035] Preferably, in the high molecular polymer C-inorganic nanoparticle composite, the content of the inorganic nanoparticles is 1-30 wt %.

[0036] Preferably, the inorganic nanoparticles are selected from at least one of oxides of Group IIA metals, sulfates of Group IIA metals, hydroxides of Group IIA metals, oxides of Group IVB metals, oxides of Group IIIA metals, hydrated alumina and silica; more preferably selected from at least one of aluminum oxide, magnesium oxide, silica, zirconium dioxide, titanium dioxide, hydrated alumina, barium sulfate and magnesium hydroxide.

[0037] Preferably, the average particle size of the inorganic nanoparticles is 10 nm-200 nm.

[0038] According to a particularly preferred embodiment of the present invention, the polymer C is the same as the polymer D and is selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate. The inventors of the present invention have found that when the polymer C is the same as the polymer D, the diaphragm material obtained by combining the fiber membrane layer with the polymer A porous membrane layer and the bonding layer has good thermal safety performance and excellent mechanical properties.

[0039] Preferably, the high molecular polymer C and the high molecular polymer D are the same and are selected from at least one of polyacrylonitrile, polyvinylidene fluoride and polyarylethersulfoneketone.

[0040] Preferably, the average thickness of the polymer A porous membrane layer is 1 μm-20 μm, more preferably 5 μm-15 μm.

[0041] Preferably, the average thickness of the adhesive layer is 0.5 μm-10 μm, more preferably 1 μm-5 μm.

[0042] Preferably, the average thickness of the fiber membrane layer is 5 μm-35 μm, more preferably 10 μm-30 μm.

[0043] Preferably, the average diameter of the core-shell structure fibers is 1 μm-2 μm, and the average diameter of the core layer fibers is 100 nm-1500 nm.

[0044] As mentioned above, the second aspect of the present invention provides a method for preparing a fiber composite diaphragm, the method comprising:

[0045] (1) subjecting component G containing polymer A to a vulcanization treatment to obtain a polymer A porous membrane, wherein the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene, and styrene-butadiene-styrene block copolymer;

[0046] (2) coating a dispersion I containing polymer B on one side of the polymer A porous membrane to form a bonding layer on one side of the polymer A porous membrane to obtain a precursor I;

[0047] (3) introducing a dispersion II containing a polymer C and inorganic nanoparticles and a dispersion III containing a polymer D into a storage device provided with an inner needle and a storage device provided with an outer needle of a coaxial electrospinning device, respectively, and performing coaxial electrospinning with the precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, wherein the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate;

[0048] (4) Drying the precursor II to obtain a fiber composite diaphragm.

[0049] According to the method described in the second aspect of the present invention, preferably, the polymer A is selected from at least one of trans-1,4-polyisoprene, high-density polyethylene, and styrene-butadiene-styrene block copolymer. According to a more preferred embodiment of the present invention, the polymer A is a composition of trans-1,4-polyisoprene and high-density polyethylene. The inventors of the present invention have found that when a combination of trans-1,4-polyisoprene and high-density polyethylene is specifically selected as polymer A, the diaphragm material obtained has better thermal safety performance.

[0050] Preferably, when polymer A is a composition of trans-1,4-polyisoprene and high-density polyethylene, based on 100 parts by weight of the total weight of the composition, in the composition, the weight ratio of the high-density polyethylene to the trans-1,4-polyisoprene is 50-90:10-50, more preferably 60-90:10-40.

[0051] Preferably, the density of the high-density polyethylene is 0.94-0.96 g / cm 3 .

[0052] Preferably, in the trans-1,4-polyisoprene, the content of the trans-1,4-structural unit is 90-99 wt %.

[0053] According to the method described in the second aspect of the present invention, preferably, in step (1), the component G also contains a water-soluble salt, sulfur and stearic acid, and relative to 100 parts by weight of the polymer A, the amount of the sulfur is 0.5-2 parts by weight, the amount of the stearic acid is 0.5-2 parts by weight, and the amount of the water-soluble salt is 1-6 parts by weight.

[0054] Preferably, the water-soluble salt is sodium chloride or potassium chloride.

[0055] Preferably, the vulcanization treatment operation includes vulcanizing and drying the component G in sequence.

[0056] Preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, wherein the conditions of the first vulcanization include: temperature 150-200°C, pressure 5-20MPa, time 5-50 minutes; the conditions of the second vulcanization include: temperature 10-50°C, pressure 5-20MPa, time 5-50 minutes.

[0057] Preferably, the drying conditions include: a temperature of 60-100° C. According to the present invention, the drying is preferably performed under vacuum conditions.

[0058] According to the method described in the second aspect of the present invention, preferably, in step (2), the polymer B is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate, and more preferably selected from at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex and carboxymethyl cellulose.

[0059] According to the present invention, the dispersion liquid I containing the polymer B may be in any form such as a solution, an emulsion, a suspension, etc. For example, the dispersion liquid I may be a styrene-butadiene latex obtained by emulsion polymerization.

[0060] According to a preferred embodiment of the present invention, the polymer B is a styrene-butadiene latex obtained by emulsion polymerization. The present invention has no particular restrictions on the specific method of obtaining the styrene-butadiene latex by emulsion polymerization, and the styrene-butadiene latex can be prepared by a conventional method for preparing styrene-butadiene latex in the art. The solid content of the styrene-butadiene latex is preferably 20-60wt%, and the particle size is preferably 50-350nm.

[0061] According to the present invention, in step (2), a micro-baking step may be optionally included after coating the polymer B.

[0062] According to the method described in the second aspect of the present invention, preferably, in step (3), in the dispersion II, the content of the inorganic nanoparticles is 1-30 wt % based on the total weight of the high molecular weight polymer C and the inorganic nanoparticles contained therein.

[0063] Preferably, in step (3), the inorganic nanoparticles are selected from at least one of oxides of Group IIA metals, sulfates of Group IIA metals, hydroxides of Group IIA metals, oxides of Group IVB metals, oxides of Group IIIA metals, hydrated alumina and silica; more preferably selected from at least one of aluminum oxide, magnesium oxide, silica, zirconium dioxide, titanium dioxide, hydrated alumina, barium sulfate and magnesium hydroxide.

[0064] Preferably, in step (3), the average particle size of the inorganic nanoparticles is 10-200 nm.

[0065] Preferably, in step (3), the polymer C and the polymer D are the same and are selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate.

[0066] Preferably, in step (3), the conditions for the coaxial electrospinning include: a spinning voltage of 15-30 kV, a receiving distance of 10-30 cm, a humidity of 20-50%, and a temperature of 20-40°C.

[0067] Preferably, in step (3), the aperture of the inner needle is 0.3-0.5 mm, and the aperture of the outer needle is 0.7-1.0 mm.

[0068] According to the method described in the second aspect of the present invention, preferably, in step (4), the drying conditions include: temperature 20-50° C., time 12-30 h.

[0069] According to the method of the second aspect of the present invention, preferably, the amount of the component G is controlled so that the thickness of the obtained polymer A porous membrane is 1 μm-20 μm, more preferably 5 μm-15 μm.

[0070] According to the method of the second aspect of the present invention, preferably, the amount of the dispersion I is controlled so that the average thickness of the obtained bonding layer is 0.5 μm-10 μm, more preferably 1 μm-5 μm.

[0071] According to the method of the second aspect of the present invention, preferably, the flow rates of the dispersion liquid II and the dispersion liquid III are independently selected from 1-15 ml / h. Preferably, the amount of the dispersion liquid II and the dispersion liquid III is controlled so that the thickness of the obtained core-shell structure fiber membrane layer is 5 μm-35 μm, more preferably 10 μm-30 μm.

[0072] According to the method of the second aspect of the present invention, preferably, the average diameter of the core-shell structure fibers is 1 μm-2 μm, and the average diameter of the core layer fibers is 100 nm-1500 nm.

[0073] According to the method according to the second aspect of the present invention, preferably, the concentrations of the dispersion II and the dispersion III are each independently selected from 2-60 wt %.

[0074] According to the method described in the second aspect of the present invention, preferably, the solvents of the dispersion II and the dispersion III are each independently selected from at least one of chloroform, N,N-dimethylformamide, tetrahydrofuran, N-methylpyrrolidone, acetone, chloroform, dichloromethane, dimethyl sulfoxide, trifluoroethanol, trifluoroacetic acid, dimethylacetamide, ethanol and hexafluoroisopropanol.

[0075] As mentioned above, the third aspect of the present invention provides a fiber composite diaphragm prepared by the aforementioned method.

[0076] As mentioned above, the fourth aspect of the present invention provides the use of the aforementioned fiber composite separator in a lithium ion battery.

[0077] In the present invention, unless otherwise specified, pressure refers to gauge pressure.

[0078] The present invention will be described in detail below through examples.

[0079] In the following examples, unless otherwise specified, all raw materials used are commercially available products.

[0080] The coaxial spinning device used below was purchased from Beijing Xinyan Hechuang Technology Co., Ltd.

[0081] Coating machine (purchased from Switzerland JENNEL, model ZAA2300)

[0082] Trans-1,4-polyisoprene was purchased from Qingdao Keda Fangtai Materials Engineering Co., Ltd. The content of trans-1,4-structure unit was 98wt%, Mw=1.14×10 5

[0083] High-density polyethylene, purchased from Qilu Petrochemical, HDPE DGDB2480, density 0.947 g / cm 3

[0084] Polyacrylonitrile, purchased from J&K Company, Mw = 1.5 × 10 5

[0085] Poly(arylethersulfoneketone), purchased from Dalian Baolimo Co., Ltd., Mw = 1×10 5

[0086] In the following examples, the average diameters of the fibers I and II in the separator were measured using NanoMeasure software in electron microscope images.

[0087] Unless otherwise specified, room temperature refers to 25±2°C.

[0088] Example 1

[0089] (1) Preparation of polymer A porous membrane

[0090] 20g of trans-1,4-polyisoprene, 73g of high-density polyethylene, 1g of sulfur, 1g of stearic acid and 5g of sodium chloride were put into a flat vulcanizer, preheated for 7 minutes at a preheating temperature of 200°C, exhausted 8 times, then hot-pressed at 10MPa for 10 minutes for a first vulcanization treatment, then cold-pressed at 10MPa for 10 minutes at room temperature for vulcanization, and the sample was taken out; the sample was placed in an ultrasonic water bath to completely dissolve the residual water-soluble salt, and then vacuum dried at a drying temperature of 60°C to obtain a polymer A porous membrane, and the average thickness of the polymer A porous membrane layer was 5μm;

[0091] (2) coating a styrene-butadiene latex (solid content 40%, particle size 130 nm) obtained by emulsion polymerization on one side of the polymer A porous membrane using a coating machine to form a bonding layer on one side of the polymer A porous membrane, wherein the average thickness of the bonding layer is 3 μm, thereby obtaining a precursor I;

[0092] (3) Dispersion II: Inorganic nanoparticles (Al2O3, average particle size of 50 nm, 2 g) were added to 10 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain an inorganic nanoparticle dispersion; polymer C (polyacrylonitrile, 20 g) was added to 68 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain a polymer C dispersion; the polymer C dispersion was added to the inorganic nanoparticle dispersion to form dispersion II, wherein the solid content of dispersion II was 22 wt %;

[0093] Dispersion liquid III: Add high molecular polymer D (polyacrylonitrile, 25 g) to 75 g of DMF solvent, and use a rotary mixer to disperse at high speed for 30 min to obtain a uniformly dispersed dispersion liquid III;

[0094] Dispersion III and dispersion II are respectively introduced into a storage device provided with an outer needle (the aperture of the needle is 1 mm) and a storage device provided with an inner needle (the aperture of the needle is 0.5 mm) of a coaxial electrospinning device, and electrospinning is performed using the incompletely dried and solidified precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, and the electrospinning conditions include: a spinning voltage of 20 kV, a receiving distance of 30 cm, a humidity of 40%, a temperature of 30° C., and flow rates of dispersions IV and V of 5 ml / h and 3 ml / h, respectively; the average thickness of the fiber membrane layer is 25 μm, the average diameter of the core-shell structure fiber is 1 μm, and the average diameter of the core layer fiber is 100 nm;

[0095] (4) The precursor II obtained in step (3) is placed in a vacuum oven and dried at room temperature for 24 hours to obtain a fiber composite diaphragm.

[0096] Example 2

[0097] (1) Preparation of polymer A porous membrane

[0098] 30g of trans-1,4-polyisoprene, 64.2g of high-density polyethylene, 1.5g of sulfur, 1.3g of stearic acid and 3g of potassium chloride were put into a flat vulcanizer, preheated for 7 minutes at a preheating temperature of 180°C, vented 7 times, then hot-pressed at 10MPa for 10 minutes for a first vulcanization treatment, then cold-pressed at 10MPa at room temperature for 10 minutes for vulcanization treatment, and the sample was taken out; the sample was placed in an ultrasonic water bath to completely dissolve the residual water-soluble salt, and then vacuum dried at a drying temperature of 60°C to obtain a polymer A porous membrane; the average thickness of the polymer A porous membrane layer was 10μm;

[0099] (2) coating a styrene-butadiene latex (solid content 40%, particle size 130 nm) obtained by emulsion polymerization on one side of the polymer A porous membrane using a coating machine to form a bonding layer on one side of the polymer A porous membrane, wherein the average thickness of the bonding layer is 2 μm, thereby obtaining a precursor I;

[0100] (3) Dispersion II: Inorganic nanoparticles (MgO, average particle size of 100 nm, 4 g) were added to 10 g of a tetrahydrofuran / N-methylpyrrolidone mixed solvent, wherein the volume ratio of tetrahydrofuran to N-methylpyrrolidone was 4:6, and the mixture was dispersed at high speed for 30 min using an auto-rotating and orbiting stirrer to obtain an inorganic nanoparticle dispersion; polymer C (polyarylethersulfoneketone, 25 g) was added to 61 g of a tetrahydrofuran / N-methylpyrrolidone mixed solvent, wherein the volume ratio of tetrahydrofuran to N-methylpyrrolidone was 4:6, and the mixture was dispersed at high speed for 30 min using an auto-rotating and orbiting stirrer to obtain a polymer C dispersion; the polymer C dispersion was added to the inorganic nanoparticle dispersion to form a dispersion II, wherein the solid content of the dispersion II was 29 wt %;

[0101] Dispersion III: Add polymer D (polyarylethersulfoneketone, 30 g) to 70 g of a tetrahydrofuran / N-methylpyrrolidone mixed solvent, where the volume ratio of tetrahydrofuran to N-methylpyrrolidone is 4:6, and use a self-rotating and revolving stirrer to disperse at high speed for 30 min to obtain a uniformly dispersed dispersion III;

[0102] Dispersion III and dispersion II are respectively introduced into a storage device provided with an outer needle (the aperture of the needle is 0.7 mm) and a storage device provided with an inner needle (the aperture of the needle is 0.3 mm) of a coaxial electrospinning device, and electrospinning is performed using the incompletely dried and solidified precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, and the electrospinning conditions include: a spinning voltage of 30 kV, a receiving distance of 35 cm, a humidity of 60%, a temperature of 40°C, and flow rates of dispersions IV and V of 4 ml / h and 3 ml / h, respectively; the average thickness of the fiber membrane layer is 20 μm, the average diameter of the core-shell structure fiber is 2 μm, and the average diameter of the core layer fiber is 500 nm;

[0103] (4) The membrane precursor II obtained in step (3) is placed in a vacuum oven and dried at room temperature for 24 hours to obtain a fiber composite membrane.

[0104] Example 3

[0105] (1) Preparation of polymer A porous membrane

[0106] 10 g of trans-1,4-polyisoprene, 85.2 g of high-density polyethylene, 1.5 g of sulfur, 1.3 g of stearic acid and 2 g of sodium chloride were put into a flat vulcanizer, preheated for 7 minutes at a preheating temperature of 200°C, exhausted 8 times, then hot-pressed at 10 MPa for 10 minutes for a first vulcanization treatment, then cold-pressed at 10 MPa for 10 minutes at room temperature for vulcanization treatment, and the sample was taken out; the sample was placed in an ultrasonic water bath to completely dissolve the residual water-soluble salt, and then vacuum dried at a drying temperature of 60°C to obtain a polymer A porous membrane, and the average thickness of the polymer A porous membrane layer was 15 μm;

[0107] (2) obtaining styrene-butadiene latex (solid content 40%, particle size 130 nm) by emulsion polymerization, and coating one side of the polymer A porous membrane with a coater to form a bonding layer on one side of the polymer A porous membrane, wherein the average thickness of the bonding layer is 1 μm, thereby obtaining a precursor I;

[0108] (3) Dispersion II: Inorganic nanoparticles (SiO2, average particle size of 150 nm, 5 g) were added to 10 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain an inorganic nanoparticle dispersion; polymer C (polyacrylonitrile, 25 g) was added to 60 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain a polymer C dispersion; the polymer C dispersion was added to the inorganic nanoparticle dispersion to form dispersion II, wherein the solid content of dispersion II was 30 wt %;

[0109] Dispersion liquid III: Add polymer D (polyacrylonitrile, 30 g) to 70 g of DMF solvent and disperse at high speed for 30 min using a self-rotating and revolving stirrer to obtain a polymer D dispersion liquid;

[0110] Dispersion III and dispersion II are respectively introduced into a storage device provided with an outer needle (the aperture of the needle is 0.7 mm) and a storage device provided with an inner needle (the aperture of the needle is 0.3 mm) of a coaxial electrospinning device, and electrospinning is performed using the incompletely dried and solidified precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, and the electrospinning conditions include: a spinning voltage of 35 kV, a receiving distance of 10 cm, a humidity of 50%, a temperature of 20°C, and flow rates of dispersions IV and V of 2 ml / h and 5 ml / h, respectively; the average thickness of the fiber membrane layer is 10 μm, the average diameter of the core-shell structure fiber is 2 μm, and the average diameter of the core layer fiber is 1000 nm;

[0111] (4) Place the precursor II obtained in step (3) in a vacuum oven and dry at room temperature for 24 hours to obtain a fiber composite diaphragm.

[0112] Example 4

[0113] A diaphragm was prepared by a method similar to that of Example 1, except that in step (1), the same weight of polyurethane (purchased from Yantai Wanhua Company, brand WHT-1495) was used to replace the polyethylene in step (1) of Example 1, and the rest was the same as in Example 1.

[0114] Example 5

[0115] A membrane was prepared by a method similar to that of Example 1, except that in step (2), the same weight of polyvinylidene fluoride (Arkema, France, trade name HSV900) was used to replace the polymer B in step (2) of Example 1, and the rest was the same as in Example 1.

[0116] Example 6

[0117] A method similar to that of Example 1 is adopted, except that in step (3), the types of polymer C and polymer D are different. Specifically, the same weight of polyarylethersulfoneketone is used to replace polymer C in step (3) of Example 1, and polymer D remains unchanged. The rest is the same as in Example 1, to prepare a diaphragm.

[0118] Comparative Example 1

[0119] A diaphragm was prepared in a manner similar to that of Example 1, except that in step (1), the same mass of polymethyl methacrylate (purchased from Sigma-Aldrich, Mw=3.5×105) was used to replace polymer A (i.e., 30 trans-1,4-polyisoprene + 73 polyethylene) in step (1) of Example 1, and the rest was the same as in Example 1, to prepare the diaphragm.

[0120] Comparative Example 2

[0121] (1) Preparation of polymer A porous membrane (same as in Example 1)

[0122] 20 g of trans-1,4-polyisoprene, 73 g of high-density polyethylene, 1 g of sulfur, 1 g of stearic acid and 5 g of sodium chloride were put into a flat vulcanizer, preheated for 7 minutes at a preheating temperature of 200° C., exhausted 8 times, then hot-pressed at 10 MPa for 10 minutes for a first vulcanization treatment, then cold-pressed at 10 MPa for 10 minutes at room temperature for vulcanization, and the sample was taken out; the sample was placed in an ultrasonic water bath to completely dissolve the residual water-soluble salt, and then vacuum dried at a drying temperature of 60° C. to obtain a polymer A porous membrane;

[0123] (2) Dispersion II: Inorganic nanoparticles (Al2O3, average particle size of 50 nm, 2 g) were added to 10 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain an inorganic nanoparticle dispersion; polymer C (polyacrylonitrile, 20 g) was added to 68 g of DMF solvent and dispersed at high speed for 30 min using an autorotating and orbiting stirrer to obtain a polymer C dispersion, and the polymer C dispersion was added to the inorganic nanoparticle dispersion to form dispersion II, wherein the solid content of dispersion II was 22 wt %;

[0124] Dispersion liquid III: Add high molecular polymer D (polyacrylonitrile, 25 g) to 75 g of DMF solvent, and use a rotary mixer to disperse at high speed for 30 min to obtain a uniformly dispersed dispersion liquid III;

[0125] Dispersion III and dispersion II are respectively introduced into a storage device provided with an outer needle (the pore size of the needle is 1 mm) and a storage device provided with an inner needle (the pore size of the needle is 0.5 mm) of a coaxial electrospinning device, and electrospinning is performed with the polymer A porous membrane layer receiving medium to form a core-shell structure fiber membrane layer on one side of the polymer A porous membrane layer to obtain a precursor II, and the electrospinning conditions include: a spinning voltage of 20 kV, a receiving distance of 30 cm, a humidity of 40%, a temperature of 30° C., and flow rates of dispersions IV and V of 5 ml / h and 3 ml / h, respectively;

[0126] (3) The precursor II obtained in step (3) is placed in a vacuum oven and dried at room temperature for 24 hours to obtain a fiber composite diaphragm.

[0127] Comparative Example 3

[0128] A diaphragm was prepared in a manner similar to that of Example 1, except that in step (3), the same mass of polycaprolactone (purchased from Jinan Daigang Technology Co., Ltd., Mw=200000) was used to replace the polymer C and the polymer D in Example 1, and the rest was the same as in Example 1.

[0129] Test Case

[0130] 1. Electrochemical performance test

[0131] The battery cycle performance and rate performance of the lithium-ion battery made from the diaphragm prepared in the above example were tested. The composition of the lithium-ion battery is as follows: the positive electrode formula is lithium iron phosphate: conductive carbon black: binder (PVDF) = 80:10:10, the negative electrode formula is graphite: conductive carbon black: binder (SBR) = 90:5:5, and the electrolyte is LiPF6 / (EC+DMC+DEC, 1:1:1, W / W / W); assembled into CR2032 button batteries, the rate performance test temperature is 25°C; the specific test results are shown in Table 1 below.

[0132] Table 1

[0133]

[0134] 2. Thermal safety and strength performance test

[0135] (1) Thermal shrinkage: The thermal shrinkage of the dimensions was measured in an oven. The sample was heat treated at 200°C for 2 h, and then the thermal shrinkage (δ) was calculated according to the formula:

[0136]

[0137] Among them, S1 and S2 are the areas of the diaphragm before and after heat treatment;

[0138] (2) Air permeability: A Gurley 4110N permeameter (USA) was used to measure the air permeability of the membrane at different temperatures (i.e., the time required for 100 mL of air to pass through the membrane). The test temperature conditions were constant temperature of 40°C, constant temperature of 110°C, and heating from room temperature to 110°C at a rate of 10°C / min and then cooling to 40°C at a rate of 10°C / min (hereinafter referred to as variable temperature).

[0139] (3) Tensile strength test: The tensile strength of the diaphragm prepared in the above example was tested using the plastic tensile test method of GB1040-79.

[0140] Table 2

[0141]

[0142] As can be seen from Table 1 above, the fiber composite diaphragm material provided by the present invention also has excellent electrochemical properties such as cycle performance and rate performance. As can be seen from Table 2, the diaphragm provided by the present invention has better comprehensive performance, especially better thermal safety performance. In particular, it can be seen from the air permeability test that the diaphragm material provided by the present invention can automatically close the pores when the temperature rises, for example, 110°C, thereby blocking the electrolyte to protect the battery, and when the temperature drops again, the diaphragm can open the channel again, so that the battery resumes normal operation.

[0143] In summary, the diaphragm material provided by the present invention has both excellent electrochemical performance and thermal safety performance.

[0144] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A fiber composite diaphragm, characterized in that: The diaphragm comprises a polymer A porous membrane layer, a fiber membrane layer, and a bonding layer located between the polymer A porous membrane layer and the fiber membrane layer; Wherein, the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene and styrene-butadiene-styrene block copolymer; The fiber membrane layer is formed by core-shell structure fibers, the material of the core layer fibers of the core-shell structure fibers is a polymer C-inorganic nanoparticle composite formed by a composite of inorganic nanoparticles and a polymer C, the material of the shell layer fibers of the core-shell structure fibers is a polymer D, and the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate; The material of the bonding layer is polymer B, and the polymer B is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate.

2. The diaphragm according to claim 1, wherein in, The polymer A is selected from at least one of trans-1,4-polyisoprene, high-density polyethylene, and styrene-butadiene-styrene block copolymer, and more preferably is a combination of trans-1,4-polyisoprene and high-density polyethylene; Preferably, in the composition, based on 100 parts by weight of the total weight of the composition, the weight ratio of the high-density polyethylene to the trans-1,4-polyisoprene is 50-90:10-50; Preferably, the polymer A porous membrane layer is obtained by vulcanizing component G containing polymer A; Preferably, the component G further contains a water-soluble salt, sulfur and stearic acid, and relative to 100 parts by weight of the polymer A, the amount of the sulfur is 0.5-2 parts by weight, the amount of the stearic acid is 0.5-2 parts by weight, and the amount of the water-soluble salt is 1-6 parts by weight; Preferably, the vulcanization treatment operation comprises vulcanizing and drying the component G in sequence; Preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, wherein the conditions of the first vulcanization include: temperature 150-200°C, pressure 5-20MPa, and time 5-50 minutes; and the conditions of the second vulcanization include: temperature 10-50°C, pressure 5-20MPa, and time 5-50 minutes.

3. The diaphragm according to claim 1 or 2, wherein: The polymer B is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate; Preferably, the polymer B is selected from at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex and carboxymethyl cellulose.

4. The diaphragm according to any one of claims 1 to 3, wherein: In the high molecular polymer C-inorganic nanoparticle composite, the content of the inorganic nanoparticles is 1-30 wt %; Preferably, the inorganic nanoparticles are selected from at least one of oxides of Group IIA metals, hydroxides of Group IIA metals, sulfates of Group IIA metals, oxides of Group IVB metals, oxides of Group IIIA metals, hydrated aluminum oxides and silicon dioxide; more preferably, selected from at least one of aluminum oxide, magnesium oxide, silicon dioxide, zirconium dioxide, titanium dioxide, hydrated aluminum oxide, barium sulfate and magnesium hydroxide; Preferably, the average particle size of the inorganic nanoparticles is 10nm-200nm; Preferably, the high molecular polymer C is the same as the high molecular polymer D and is selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate.

5. The diaphragm according to any one of claims 1 to 4, wherein: The average thickness of the polymer A porous membrane layer is 1 μm-20 μm, preferably 5 μm-15 μm; Preferably, the average thickness of the bonding layer is 0.5 μm-10 μm, more preferably 1 μm-5 μm; Preferably, the average thickness of the fiber membrane layer is 5 μm-35 μm, more preferably 10 μm-30 μm; Preferably, the average diameter of the core-shell structure fibers is 1 μm-2 μm, and the average diameter of the core layer fibers is 100 nm-1500 nm.

6. A method for preparing a fiber composite diaphragm, characterized in that: The method includes: (1) subjecting component G containing polymer A to a vulcanization treatment to obtain a polymer A porous membrane, wherein the polymer A is selected from at least one of trans-1,4-polyisoprene, butadiene rubber, natural rubber, styrene-butadiene rubber, polyurethane, high-density polyethylene, and styrene-butadiene-styrene block copolymer; (2) coating a dispersion I containing polymer B on one side of the polymer A porous membrane to form a bonding layer on one side of the polymer A porous membrane to obtain a precursor I; (3) introducing a dispersion II containing a polymer C and inorganic nanoparticles and a dispersion III containing a polymer D into a storage device provided with an inner needle and a storage device provided with an outer needle of a coaxial electrospinning device, respectively, and performing coaxial electrospinning with the precursor I as a receiving medium to form a core-shell structure fiber membrane layer on the bonding layer of the precursor I to obtain a precursor II, wherein the polymer C and the polymer D are each independently selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate; (4) Drying the precursor II to obtain a fiber composite diaphragm.

7. The method according to claim 6, wherein: In step (1), the polymer A is selected from at least one of trans-1,4-polyisoprene, high-density polyethylene, and styrene-butadiene-styrene block copolymer; more preferably, it is a combination of trans-1,4-polyisoprene and high-density polyethylene; Preferably, in the composition, based on 100 parts by weight of the total weight of the composition, the weight ratio of the high-density polyethylene to the trans-1,4-polyisoprene is 50-90:10-50; Preferably, the component G further contains a water-soluble salt, sulfur and stearic acid, and relative to 100 parts by weight of the polymer A, the amount of the sulfur is 0.5-2 parts by weight, the amount of the stearic acid is 0.5-2 parts by weight, and the amount of the water-soluble salt is 1-6 parts by weight; Preferably, the vulcanization treatment operation comprises vulcanizing and drying the component G in sequence; Preferably, the vulcanization includes sequentially performing a first vulcanization and a second vulcanization, wherein the conditions of the first vulcanization include: temperature 150-200°C, pressure 5-20MPa, and time 5-50 minutes; and the conditions of the second vulcanization include: temperature 10-50°C, pressure 5-20MPa, and time 5-50 minutes.

8. The method according to claim 6, wherein: In step (2), the polymer B is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex, styrene-acrylic latex, carboxymethyl cellulose, chitosan, cyclodextrin and sodium alginate; Preferably, the polymer B is selected from at least one of a copolymer of vinylidene fluoride and hexafluoropropylene, polyurethane, styrene-butadiene latex and carboxymethyl cellulose.

9. The method according to any one of claims 7 to 8, wherein: In step (3), in the dispersion II, the content of the inorganic nanoparticles is 1-30 wt % based on the total weight of the high molecular weight polymer C and the inorganic nanoparticles contained therein; Preferably, the inorganic nanoparticles are selected from at least one of oxides of Group IIA metals, sulfates of Group IIA metals, hydroxides of Group IIA metals, oxides of Group IVB metals, oxides of Group IIIA metals, hydrated aluminum oxides and silicon dioxide; more preferably, selected from at least one of aluminum oxide, magnesium oxide, silicon dioxide, zirconium dioxide, titanium dioxide, hydrated aluminum oxide, barium sulfate and magnesium hydroxide; Preferably, the average particle size of the inorganic nanoparticles is 10-200 nm.

10. The method according to any one of claims 7 to 9, wherein: In step (3), the polymer C is the same as the polymer D and is selected from at least one of polyacrylonitrile, polyvinylidene fluoride, polyarylethersulfoneketone and polyethylene terephthalate; Preferably, the conditions for the coaxial electrospinning include: a spinning voltage of 15-30 kV, a receiving distance of 10-30 cm, a humidity of 20-50%, and a temperature of 20-40°C.

11. A fiber composite diaphragm prepared by the method according to any one of claims 6 to 10.

12. Use of the fiber composite diaphragm according to any one of claims 1 to 5 and 11 in lithium ion batteries.